Internal mechanism and enhancement strategy of chemical industry carbon emission reduction promoted by the development of digital economy - Gao, Ruiyan; Ni, Taohan; Zhang, Qin; Zhou, Yixin; Yang, Bohan; Mao, Qizhe (Frontiers in Environmental Science, 2025)
IntroductionWith the rapid development of the economy in recent years, along with global warming, the chemical industry is an important contributor to global carbon emissions. The rapid development of the digital economy has in turn brought new opportunities for chemical companies to reduce emissions. In this study, chemical industry enterprises are taken as the research object, aiming to explore how the development of digital economy has a specific impact on the carbon emission intensity of the chemical industry through the paths of enhancing the efficiency of resource utilization and optimizing the industrial structure.MethodsTo analyze the carbon emissions of the chemical industry, we first applied decoupling, quadratic, and cubic models to measure emission trends. The impact mechanisms were then examined using externality theory and enterprise environmental behavior theory, focusing on industrial enterprises in prefecture-level cities. The influence of the digital economy on carbon emissions was assessed through baseline regression analysis and robustness tests.Results(1) digital economy development can reduce carbon emission intensity; (2) The higher the level of digital economy development, the greater the degree of digitization and informatization across society, the more efficient the resource utilization by chemical enterprises, and the stronger the push towards green and low-carbon industry, all of which contribute to reducing carbon emission intensity.DiscussionThe results demonstrate that digital transformation plays a crucial role in reducing carbon emissions in the chemical industry. Enhanced digitalization enables enterprises to optimize production processes, increase energy efficiency, and adopt cleaner technologies. To further promote emission reductions, chemical enterprises should increase R&D investment in digital and green technologies, form innovation alliances to accelerate knowledge sharing, and pursue strategic transformation toward low-carbon business models.